ANALISIS KEPUTUSAN PEMBELIAN JASA PENAMBANGAN PT BERAU COAL KEPADA PT BUKIT MAKMUR MANDIRI UTAMA (BUMA) - Arifin Sitio; Beni Rasjid (Master of Management, Mataram University, 2018)
This study aims to find out the influence of the quality of services, people, processes and physical evidence on the decision to purchase mining services by PT Berau Coal to PT BUMA. In this study, data collection was carried out through survey methods by distributing questionnaires to respondents within the company organization PT Berau Coal starting from the position of supervisor /engineer to general manager. The number of samples taken in this study was 50 people. Thetechnique sampling used in this study is Simple Random Sampling. Data analysis method uses multiple regression analysis with SPSS 23.0. The results of data processing show that the variable quality of services, people, processes and physical evidence affect the decision to purchase mining services. Parameters for testing the effect of service quality on service purchasing decisions show a t value of 3.191 (sig = 0.003), the influence of people on the decision to purchase services shows a t value of 2.341 (sig = 0.024), the effect of the process on the decision to purchase services shows a t value of 2.400 ( sig = 0.021), and the effect of physical evidence on the decision to purchase services shows a t value of 2.797 (sig = 0.008). Penelitian ini bertujuan untuk mengetahui pengaruh kualitas layanan, orang, proses dan bukti fisik terhadap keputusan pembelian jasa penambangan oleh PT Berau Coal kepada PT BUMA. Dalam penelitian ini, pengumpulan data dilakukan melalui metode survei dengan menyebarkan kuesioner kepada responden dalam organisasi perusahaan PT Berau Coal mulai dari posisi supervisor / insinyur hingga general manager. Jumlah sampel yang diambil dalam penelitian ini adalah 50 orang. Teknik sampling yang digunakan dalam penelitian ini adalah Simple Random Sampling. Metode analisis data menggunakan analisis regresi berganda dengan SPSS 23.0. Hasil pengolahan data menunjukkan bahwa variabel kualitas layanan, orang, proses dan bukti fisik mempengaruhi keputusan untuk membeli jasa penambangan. Parameter untuk menguji pengaruh kualitas layanan pada keputusan pembelian layanan menunjukkan pada nilai 3,191 (sig = 0,003), pengaruh orang pada keputusan untuk membeli layanan menunjukkan pada nilai 2,331 (sig = 0,024), efek dari proses pada keputusan untuk membeli layanan menunjukkan pada nilai 2.400 (sig = 0,021), dan pengaruh bukti fisik pada keputusan untuk membeli layanan menunjukkan pada nilai 2,797 (sig = 0,008).Keywords : Quality of services, people, processes and physical evidence, service purchasing decisions